Evaluating service quality of the mobile operator Mobilis using the SERVPERF Model: A study on a sample of Mobilis customers at the Laghouat Agency - Lakhdar, Rinouba; Mohammed, Cheknane (The International tax journal, 2025)
This study aims to evaluate the service quality provided by the mobile operator Mobilis in the Wilaya of Laghouat using the SERVPERF model. A field study was conducted on a randomly selected sample of 112 Mobilis customers in the region. The statistical software SPSS 26 was used to analyze the questionnaire data, present the results, and test the hypotheses. The study found that the service quality delivered by the company under investigation, across its five SERVPERF dimensions (reliability, tangibility, responsiveness, empathy, and assurance)—met customer expectations.